Dad, what's for dinner? : lifesaving recipes to avoid meltdowns, have fun in the kitchen, and keep your kids well fed - Nayfeld, David; Stein, Joshua David (Alfred A. Knopf, 2025)
"A cookbook of recipes for fathers, for cooking for and with children"--